2017
DOI: 10.1155/2017/2852514
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of Cerebral Oxygenation by Aortic Arch Calcification Progression in Patients Undergoing Hemodialysis: A Cross-Sectional Study

Abstract: Background Near-infrared spectroscopy revealed that the regional saturation of oxygen (rSO2) in cerebral tissue is lower in hemodialysis (HD) patients than in healthy subjects. However, no study has examined the changes in cerebral oxygenation by aortic arch calcification (AAC) progression in HD patients. Methods A total of 104 HD patients were divided into four groups by AAC grade determined using chest radiography: 23 patients at grade 0, 24 at grade 1, 30 at grade 2, and 27 at grade 3. Differences in clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Concerning the vascular injury in CKD patients, the onset of CKD, which even occurred in early stages, stimulated aortic calcification in rat CKD models with mild or moderate renal injury [ 26 ], and aortic arch calcification was not only a consequence of CKD but also a predictor of renal function progression in CKD G3 to G5 patients [ 27 ]. Furthermore, recently in HD patients, cerebral rSO 2 significantly decreased according to the progression of aortic arch calcification because of a decreased oxygen supply in the brain via cerebral macro- and/or microcirculation impairments [ 28 ]. Thus, even in the CKD patients enrolled in this study, cerebral rSO 2 deterioration might have occurred due to cerebral vascular injury, including calcification associated with CKD progression itself, although we could not comment on the association between cerebral oxygenation and vascular injury with CKD patients because no examination was conducted to investigate vascular injury or calcification in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the vascular injury in CKD patients, the onset of CKD, which even occurred in early stages, stimulated aortic calcification in rat CKD models with mild or moderate renal injury [ 26 ], and aortic arch calcification was not only a consequence of CKD but also a predictor of renal function progression in CKD G3 to G5 patients [ 27 ]. Furthermore, recently in HD patients, cerebral rSO 2 significantly decreased according to the progression of aortic arch calcification because of a decreased oxygen supply in the brain via cerebral macro- and/or microcirculation impairments [ 28 ]. Thus, even in the CKD patients enrolled in this study, cerebral rSO 2 deterioration might have occurred due to cerebral vascular injury, including calcification associated with CKD progression itself, although we could not comment on the association between cerebral oxygenation and vascular injury with CKD patients because no examination was conducted to investigate vascular injury or calcification in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of cerebral rSO 2 by NIRS has recently been performed in various clinical settings, including cardiovascular surgery, pediatrics, and dialysis [3][4][5][6][7][8][16][17][18]. We therefore, reviewed the literature for reports of cerebral rSO 2 values in dialysis patients (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Near-infrared spectroscopy (NIRS) has recently been used to measure regional saturation of oxygen (rSO 2 ), as a marker of tissue oxygenation. In particular, cerebral rSO 2 was measured in patients in various clinical settings, including hemodialysis (HD) patients [3][4][5][6][7][8]. It would be considered important to maintain cerebral rSO 2 levels because that low cerebral rSO 2 has been associated with cognitive impairment in patients with chronic kidney disease (CKD) [5,8] and poor neurologic outcomes in post-cardiac arrest patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study including 49 patients (9 hemodialysis and 40 nonhemodialysis) that underwent coronary artery bypass graft surgery, hemodialysis patients had lower rSO 2 levels, even after adjusting for age, hemoglobin, and LV ejection fraction [97]. A cross-sectional study including 104 hemodialysis patients indicated that cerebral rSO 2 significantly decreased as aortic-arch calcification progressed and was independently associated with serum phosphate and history of smoking [98]. Finally, studies evaluating cerebral oxygenation during dialysis session have shown that cerebral oxygenation deteriorates after the beginning of hemodialysis [93, 99]; cerebral ischemia cannot be predicted from BP alterations during dialysis, and this leads to high risk of stroke and cognitive dysfunction development [100, 101].…”
Section: Assessment Of Endothelial Dysfunction In Ckd: Functional Metmentioning
confidence: 99%